Geomorphological study of Thera and Akrotiri archaeological site. - Gournelos, Th.; Evelpidou, N.; Vassilopoulos, A.; Chartidou, K. (Geoinformation technologies for geocultural landscapes: European perspectives, 2007)
This chapter concerns the application of computing technologies in Geoarchaeology. The main issue is the combination of GIS and remote sensing technologies with on-site observations of the archaeological, geomorphological and geological characteristics of the area. This combination involves gathering all the necessary information of the spatial structures: geological, topographical, geomorphological and archaeological data. The main target is the composition of the palaeolandscape in order to reveal the paleotopography of Thera and the archaeological site of Akrotiri before the Minoan eruption. GIS analytical tools may help to recreate the different phases of landform evolution of Thera before the Minoan era till nowadays. Thus, 3D models before the Minoan, during the Minoan and after the Minoan phase were produced. Furthermore, the chapter focuses on the geomorphology of Akrotiri site, the most important archaeological site on Thera. The geological formations and the dominant erosion and deposition processes were mapped in order to understand the geomorphological evolution of the area. The extensive reworking and adaptation of the geomorphology from sustained volcanic activity over a long period has resulted in huge physical changes: loss of a central area of the island, coastline modifications, soil loss, deposition and abandonment of valleys and settlement sites. This abrupt evolution have played a major role to the land use change and land cultivation, strongly affecting the local communities, perhaps emphasising and coinciding with distinctive periods of cultural expansion and contraction.